2002
DOI: 10.1177/0148607102026006333
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte growth factor stimulates the recovery of epithelial structure and function in a mouse model of total parenteral nutrition

Abstract: KGF administration reversed many of the adverse epithelial changes associated with TPN administration. Additionally, KGF up-regulated epithelial KGF receptor expression. It is possible that KGF may have a therapeutic efficacy in patients who are receiving TPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
4
17
0
Order By: Relevance
“…It is possible that a cytokine imbalance prevails with administration of TPN, or with SBS, which may result in the observed altered expression of KGF. In recent studies, exogenous KGF reversed the villus atrophy observed in rodent starvation and TPN models (12,13,47,53). In our mouse TPN model, villus atrophy occurred simultaneous with a 2-fold decline in KGF mRNA expression.…”
Section: Discussionsupporting
confidence: 55%
“…It is possible that a cytokine imbalance prevails with administration of TPN, or with SBS, which may result in the observed altered expression of KGF. In recent studies, exogenous KGF reversed the villus atrophy observed in rodent starvation and TPN models (12,13,47,53). In our mouse TPN model, villus atrophy occurred simultaneous with a 2-fold decline in KGF mRNA expression.…”
Section: Discussionsupporting
confidence: 55%
“…Protein was extracted from isolated IEL, and immunoblots performed using a Bio-Rad protein assay kit (Bio-Rad Laboratories, Hercules, CA) with standard methods. 33 Purified biotinylated anti-mouse ACE (R&D Systems, Inc., Mineapolis, MN) (at a concentration of 0.1 µg/ml diluted in blocking solution (Zymed Laboratories, Inc., San Francisco, CA) was used for ACE detection. This was followed by an application of horse radish peroxidase-streptavidin conjugate (1:5000 dilution; Zymed).…”
Section: Animal Modelmentioning
confidence: 99%
“…IEL are a distinct population of T-lymphocytes that reside above the basement membrane and lie between ECs, which line the intestinal lumen. Previous studies have shown that IEL play an important role in the maintenance of the gut barrier function, and support intestinal EC growth through production of KGF [24,26]. In a reciprocal fashion, growth and function of IEL has been shown to be dependent on the expression of a series of cytokines, particularly interleukin-7 (IL-7), which is produced by ECs, predominately after they have differentiated into goblet cells [27,28].…”
Section: Introductionmentioning
confidence: 99%